High major histocompatibility complex class I polymorphism despite bottlenecks in wild and domesticated populations of the zebra finch (Taeniopygia guttata) - Newhouse, Daniel J. (BMC Evol Biol, 2015)
BACKGROUND: Two subspecies of zebra finch, Taeniopygia guttata castanotis and T. g. guttata are native to Australia and the Lesser Sunda Islands, respectively. The Australian subspecies has been domesticated and is now an important model system for research. Both the Lesser Sundan subspecies and domesticated Australian zebra finches have undergone population bottlenecks in their history, and previous analyses using neutral markers have reported reduced neutral genetic diversity in these populations. Here we characterize patterns of variation in the third exon of the highly variable major histocompatibility complex (MHC) class I α chain. As a benchmark for neutral divergence, we also report the first mitochondrial NADH dehydrogenase 2 (ND2) sequences in this important model system. RESULTS: Despite natural and human-mediated population bottlenecks, we find that high MHC class I polymorphism persists across all populations. As expected, we find higher levels of nucleotide diversity in the MHC locus relative to neutral loci, and strong evidence of positive selection acting on important residues forming the peptide-binding region (PBR). Clear population differentiation of MHC allele frequencies is also evident, and this may be due to adaptation to new habitats and associated pathogens and/or genetic drift. Whereas the MHC Class I locus shows broad haplotype sharing across populations, ND2 is the first locus surveyed to date to show reciprocal monophyly of the two subspecies. CONCLUSIONS: Despite genetic bottlenecks and genetic drift, all surveyed zebra finch populations have maintained high MHC Class I diversity. The diversity at the MHC Class I locus in the Lesser Sundan subspecies contrasts sharply with the lack of diversity in previously examined neutral loci, and may thus be a result of selection acting to maintain polymorphism. Given uncertainty in historical population demography, however, it is difficult to rule out neutral processes in maintaining the observed diversity. The surveyed populations also differ in MHC Class I allele frequencies, and future studies are needed to assess whether these changes result in functional immune differences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-015-0546-3) contains supplementary material, which is available to authorized users.